2003
DOI: 10.1046/j.1365-2958.2003.03464.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication of a restriction–modification gene complex

Abstract: SummaryPrevious works have suggested that some gene complexes encoding a restriction (R) enzyme and a cognate modification (M) enzyme may behave as selfish mobile genetic elements. RM gene complexes, which destroy 'non-self' elements marked by the absence of proper methylation, are often associated with mobile genetic elements and are involved in various genome rearrangements. Here, we found amplification of a restriction-modification gene complex. Bam HI gene complex inserted into the Bacillus chromosome show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 53 publications
(80 reference statements)
1
44
0
Order By: Relevance
“…For example, homologous recombination can mediate competition between resident and incoming stretches of DNA Handa et al 2001;Sadykov et al 2003;Mochizuki et al 2006). Regions of DNA encoding TA-like restrictionmodification systems can displace those that do not, but not vice versa Handa et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, homologous recombination can mediate competition between resident and incoming stretches of DNA Handa et al 2001;Sadykov et al 2003;Mochizuki et al 2006). Regions of DNA encoding TA-like restrictionmodification systems can displace those that do not, but not vice versa Handa et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it was observed that an R-M gene complex residing on a bacterial chromosome cannot be replaced easily by a homologous sequence of DNA (102,103), indicating that they are difficult to eliminate. Furthermore, it was observed that R-M systems are often linked to mobile elements or acquired through HGT (99).…”
Section: Stabilization Of Genomic Islandsmentioning
confidence: 99%
“…An addiction module found on plasmids, prophages, integrons, and other mobile elements would help their stable maintenance, and, in general, an addiction module would stabilize maintenance of any linked genomic region (5,8,21,32,58,64). Indeed, a theoretical work demonstrated that an addiction module can defeat its competitor and spread in a population in the presence of space structure (47).…”
mentioning
confidence: 99%
“…Such RM systems with demonstrated capacity for postsegregational killing include PaeR7I, EcoRI, EcoRV, and SsoII (7,36,48,49). Chromosomally placed RM gene complexes (PaeR7I and BamHI) also resist replacement by an allelic DNA (21,58). However, the level of such killing varies among RM systems, presumably reflecting the complexity of the parasite-host interaction (and we will analyze one example in the present work).…”
mentioning
confidence: 99%
See 1 more Smart Citation